Durability of porous glasses - Rodríguez Valdivieso, Christian Raúl (Pontificia Universidad Católica del Perú, 2022)
The investigations of this work are dedicated to the production of highly alkali resistant porous glasses, evaluating the effect of adding ZrO2 to the sodium borosilicate Vycortype glass. The additions were made with the purpose of improving the ability of the silica porous structure to withstand alkaline solutions. Base glasses (BG) with 0 mol% ZrO2 (Zr0), 3 mol% ZrO2 (Zr3) and 6 mol% ZrO2 (Zr6) were produced by the conventional melting and quenching method. The vitreous structure of the BG was confirmed by XRD. Further characterization tests such as density, ATR and DSC were performed as well. To induce spinodal phase separation and create a two-phase matrix (an insoluble silica rich phase and a soluble sodium-borate phase), BG were heat treated at different temperatures from 560 °C to 700 °C for 12 hours. Scanning electron microscopy (SEM) confirmed the expected interconnected sponge-like morphology. Pore sizes were calculated according to the DIN EN ISO 13383 norm. There is a well-defined tendency of pore size growth with increasing heat treatment temperature and time for 0 mol% ZrO2 and 3 mol% ZrO2 glasses. SEM images also show a decrease in pore size when ZrO2 is added to the glass. The 6 mol% ZrO2 glass did not show spinodal phase separation. Based on the pore size results, a heat treatment temperature of 680 °C was chosen for the following tests. To obtain a porous sample, the soluble sodium-borate phase needs to be leached with HCl solution. For this, leaching temperature and the HCl solution were varied, as well as the subsequent drying process.The best leaching results were obtained with a solution of 1 M HCl + 70 % Ethanol (ratio 9:1) at room temperature for two days and 2 M HCl + 70 % Ethanol (ratio 9:1) at 70 °C for seven days, for Zr0 and Zr3, respectively. To study the durability of porous glasses, alkali resistance tests against 0.1 M NaOH were carried out. It was shown that the alkali stability of Zr0 glass is very low (mass loss of about 20 % in 22 hours). However, when 3 mol% ZrO2 is added to the glass the weight loss percentage is reduced significantly (mass loss of about 4 % in 22 hours). It was found that the presence of zirconia in the silica rich porous structure improves the stability against alkali dramatically. A big problem is the leaching of the phase separated glasses, which very often resulted in breaking of the samples.

Las investigaciones de este trabajo se basan en la producción de vidrios porosos altamente resistentes a los álcalis, evaluando el efecto de la adición de ZrO2 al vidrio borosilicato de sodio tipo Vycor. Las adiciones se realizaron con el propósito de mejorar la capacidad de la estructura porosa de sílice para resistir soluciones alcalinas. Se produjeron vidrios base (BG) de 0 % mol ZrO2 (Zr0), 3 % mol ZrO2 (Zr3), 6 % mol ZrO2 (Zr6) mediante el método convencional de fusión y enfriamiento. La estructura amorfa de BG fue confirmada por DRX. También se realizaron más pruebas de caracterización como densidad, ATR y DSC. Para inducir la separación de fases espinodal y crear una matriz de dos fases (una fase insoluble rica en sílice y una fase soluble de borato de sodio), se trataron térmicamente BG a diferentes temperaturas de 560 °C a 700 °C durante 12 horas. La microscopía electrónica de barrido (SEM) confirmó la morfología esperada similar a una esponja interconectada. Los tamaños de los poros se calcularon según la norma DIN EN ISO 13383. Existe una tendencia bien definida de crecimiento del tamaño de los poros con el aumento de la temperatura y el tiempo del tratamiento térmico para vidrios con 0 % mol ZrO2 y 3 % mol ZrO2. Las imágenes SEM también muestran una disminución en el tamaño de los poros cuando se agrega ZrO2 al vidrio. El vidrio de ZrO2 al 6 % en moles no mostró separación de fases espinodal. Basándose en los resultados del tamaño de los poros, se eligió una temperatura de tratamiento térmico de 680 °C para las siguientes pruebas. Para obtener una muestra porosa, la fase soluble de borato de sodio debe lixiviarse con una solución de HCl. Para ello se varió la temperatura de lixiviación y la solución de HCl, así como el posterior proceso de secado, los mejores resultados de lixiviación se obtuvieron con una solución de 1 M HCl + Etanol al 70 % (proporción 9: 1) a temperatura ambiente durante dos días y 2 M HCl + etanol al 70 % (proporción 9: 1) a 70 °C durante siete días, para Zr0 y Zr3, respectivamente. Para estudiar la durabilidad de los vidrios porosos, se llevaron a cabo pruebas de resistencia a los álcalis frente a 0.1 M NaOH. Se demostró que la estabilidad alcalina del vidrio Zr0 es muy baja (pérdida de masa de aproximadamente el 20 % en 22 horas). Sin embargo, si se añade al vidrio un 3 % en moles de ZrO2, el porcentaje de pérdida de peso se reduce significativamente (pérdida de masa de aproximadamente 4 % en 22 horas). Se encontró que la presencia de zirconia en la estructura porosa rica en sílice mejora la estabilidad frente a los álcalis drásticamente. Un gran problema es la lixiviación de los vidrios con separación de fases, que muy a menudo provoca la rotura de las muestras.
Keywords: Vidrio; Materiales porosos; Resistencia de materiales; https://purl.org/pe-repo/ocde/ford#2.05.01